Trends in Modern Cosmology - Jesse Capistrano de Souza, Abraao (IntechOpen, 2017)
The modern cosmology has been turned into an outstanding field of active research through the years. Today, we have more scientific data in modern cosmology than we could get rid of it, which makes the present days an exciting era for scientific knowledge. "Trends in Modern Cosmology" invites the reader to tackle the big questions of the universe from cultural aspects of cosmology and its influence on arts, philosophy, and politics to more specialized technical advances in the field as the physics of dark sector, black holes, galaxies, large structure formation, and particles. In fact, it reveals our endless searching for the better understanding of the universe as a legacy of knowledge for next generations.